KESIAPAN BELAJAR ANAK MEMASUKI SEKOLAH DASAR - Indah Fajrotuz Zahro; Abd. Hafid; Eva Nur Fadilah (Prodi. Pendidikan Islam Anak Usia Dini, Institut Pesantren KH. Abdul Chalim, 2022)
This study aims to determine the description of the learning readiness of RA Al Ulum group B students entering elementary school. Researchers used descriptive qualitative research methods with data collection techniques in the form of observations and interviews with primary data sources 19 students and secondary data from teachers and documentation. Based on the results of the study, the readiness of early childhood learning to enter elementary school can be based on the criteria that children must be able to work together and no longer depend a lot on their mother in activities, children are able to make observations, children must be able to realize the interests of others, curiosity, energy who are abundant in social feelings, can think abstractly, have an interest in doing their learning tasks, and are attentive. Based on the results of observations and interviews with research subjects, information was obtained that students of RA Al Ulum Kabalan had the criteria for the maturity of children entering elementary school with the highest category is on the criteria of sufficient student energy, followed by the criteria of curiosity, interest in students' hobbies, awareness of the interests of others, observation skills, social feelings, attachment to parents/caregivers, abstract thinking skills and attention. Children's learning readiness can be done by providing guidance services individually/ groups to support various factors in learning readiness which are not only carried out by teachers in the school environment, but by collaborating with parents to play their roles as teachers, facilitators, motivators and mentors. Abstrak Penelitian ini bertujuan untuk mengetahui deskripsi kesiapan belajar siswa RA Al Ulum kelompok B memasuki sekolah dasar. Peneliti menggunakan metode penelitian kualitatif deskriptif dengan teknik pengumpulan data berupa observasi dan wawancara dengan sumber data primer 19 siswa dan data sekunder dari guru dan dokumentasi. Berdasarkan hasil penelitian Kesiapan belajar anak usia dini memasuki sekolah dasar dapat berdasarkan kriteria anak harus sudah dapat bekerja sama dan tidak lagi banyak tergantung dengan ibunya dalam kegiatan, anak mampu melakukan pengamatan, anak harus sudah mampu menyadari akan kepentingan orang lain, rasa ingin tahu, energi yang melimpah perasaan kesosialan, dapat berpikir abstrak, memiliki minat dalam melakukan tugas belajarnya, dan perhatian. Berdasarkan hasil observasi dan wawancara subjek penelitian diperoleh infomasi bahwa siswa RA Al Ulum Kabalan memiliki kriteria kematangan anak memasuki sekolah dasar dengan kategori paling tinggi ada pada kriteria energi siswa yang berkecukupan, diikuti dengan kriteria rasa ingin tahu, minat pada kegemaran siswa, kesadaran akan kepentingan orang lain, kemampuan pengamatan, perasaan kesosialan, kelekatan dengan orang tua/ pengasuh, kemampuan berpikir abstrak dan perhatian. Kesiapan belajar anak dapat dilakukan dengan memberikan layanan bimbingan secara individu atau kelompok untuk menunjang berbagai faktor dalam kesiapan belajar yang tidak hanya dilakukan oleh guru di lingkungan sekolah, tetapi dengan bekerjasama dengan orang tua untuk memainkan perannya sebagai guru, fasilitator, motivator dan pembimbing.